Unveiling the occurrence of diabetic ketoacidosis with SGLT2 Inhibitors: need for vigilance and careful monitoring - Mannava, Anjali Srikanth; Harikrishnan, Samyuktha; Srinivas, Swathi; Boyapati, Sri Pranvi (International Journal of Advances in Medicine, 2023)
With great interest, we have read the case report titled “Euglycemic diabetic ketoacidosis (DKA)-a rare side effect of sodium-glucose co-transporter-2 inhibitor in a patient of type 2 diabetes mellitus with left ventricular dysfunction: a case report” published in the international journal of advances in medicine.